Anna Freud Bernays papers - Bernays, Anna Freud, 1858-1955.; Bernays, Anna Freud, 1858-1955.
Correspondence, writings, speech, guest books, clippings, and photographs of Bernays's children. Correspondence consists mainly of letters to Bernays from members of the Bernays and Freud families including her husband Ely Bernays, her mother Amalia Freud, and her sister-in-law Martha Freud. Also includes page proofs of Bernays's autobiography entitled, Erlebtes (1938).
Sister of Sigmund Freud.
Collection material in English and German.
Forms part of: Sigmund Freud collection.
Keywords: Bernays, Ely -- Correspondence; Freud, Amalia, -- 1835-1929 -- Correspondence; Freud, Martha, -- 1861-1951 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Bernays family -- Correspondence; Freud family -- Correspondence